Microbe-mineral interactions in the Plastisphere: Coastal biogeochemistry and consequences for degradation of plastics - Dodhia, Maya S.; Rogers, Kelsey L.; Fernández-Juárez, Victor; Carreres-Calabuig, Joan A.; Löscher, Carolin R.; Tisserand, Amandine A.; Keulen, Nynke; Riemann, Lasse; Shashoua, Yvonne; Posth, Nicole R. (Frontiers in Marine Science, 2023)
Microbe-mineral interactions, such as mineral substrate utilization and aggregate formation, have played a key role in the cycling of elements through Earth evolution. In water, soils, and sediment biogeochemistry modulates microbial community composition and mineral formation over spatial and temporal scales. Plastic is a new material that is now widespread in the environment. Both microbial and mineral associations with plastic comprise the Plastisphere, which influences the fate of plastic. This study focuses on how the biogeochemical environment defines microbial and mineral association with polyethylene (PE) and polystyrene (PS) over a 12-month period in a temperate coastal harbor. The coastal harbor environment was separated into 3 conceptual compartments defined by physical and biogeochemical conditions, that allow transfer of electrons between species e.g., light penetration and redox setting. Microbe and mineral association were investigated in the water column, top sediment, and bottom sediment by applying a range of modern analytical techniques to identify changes in the chemical structures of plastics, microbial community development, metal, salt and mineral formation. The epiplastic microbial community was distinct to that of the surrounding environment across changing redox conditions. The type and oxidation state of metallic minerals formed on plastics or entrapped in the biofilm matrix related to the dominant abiotic and biotic processes across redox conditions. FTIR spectroscopy indicated the occurrence of PE and PS oxidation in the various biogeochemical environments. Combined, these findings demonstrate that redox conditions and surrounding biogeochemistry mediate the composition of mineralogical and biological loading of PE and PS in coastal marine environments. This suggests that the biogeochemical setting in which the plastics are stored constrains the development of plastic interfacial biogeochemistry and the potential for plastic degradation and transport over time.